2016
DOI: 10.1016/j.astropartphys.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of near-earth thunderstorms electric field on the intensity of ground cosmic ray positrons/electrons in Tibet

Abstract: Monte Carlo simulations are performed to study the correlation between the ground cosmic ray intensity and near-earth thunderstorms electric field at YBJ (4300 m a.s.l., Tibet, China).The variations of the secondary cosmic ray intensity are found to be highly dependent on the strength and polarity of the electric field. In negative fields and in positive fields greater than 600 V/cm, the total number of ground comic ray positrons and electrons increases with increasing electric field strength. And these values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…The dependence of TGEs on the sign of vertical component of electric field, found in our observations and previous study by Kudela et al (2017), was also discussed by Lidvansky (2003), Khaerdinov et al (2005) and Bartoli et al (2018). Bartoli et al (2018) analyzed observations in Tibet, China, at the altitude of 4300 m and performed simulations using CORSIKA code to investigate the development of secondary electrons and positrons following the hypothesis introduced by Zhou et al (2016). They conclude that the enhancements of secondary cosmic rays are more frequent for negative PG because of the initial abundance of electrons with respect to positrons in the Earth's atmosphere.…”
Section: Discussionsupporting
confidence: 73%
“…The dependence of TGEs on the sign of vertical component of electric field, found in our observations and previous study by Kudela et al (2017), was also discussed by Lidvansky (2003), Khaerdinov et al (2005) and Bartoli et al (2018). Bartoli et al (2018) analyzed observations in Tibet, China, at the altitude of 4300 m and performed simulations using CORSIKA code to investigate the development of secondary electrons and positrons following the hypothesis introduced by Zhou et al (2016). They conclude that the enhancements of secondary cosmic rays are more frequent for negative PG because of the initial abundance of electrons with respect to positrons in the Earth's atmosphere.…”
Section: Discussionsupporting
confidence: 73%
“…Clear asymmetry in polarity of E is indicated for the total electron/positron component. Although the altitude of LS is smaller than that for the position of Tibet CR station, Figure 5 of paper by Zhou et al () indicates about 65% of electrons and 35% of positrons in the total number of e + , e − component for zero electric field at the atmospheric depth of 600 g/cm 2 . Based on the curves in the cited figure, it is expected that the relative contribution of electrons is probably higher at the depth of LS (780 g/cm 2 ).…”
Section: Discussionmentioning
confidence: 86%
“…However, without knowledge of the electric field structure in the thunderstorm cloud, its position and motion with respect to the peak of Lomnický štít where the measurements are running, it is difficult to test such hypothesis. Thus, the suggested explanation of the asymmetry between number of events for negative and positive polarities of electric field, based on the theoretical paper by Zhou et al (), should be considered as one of possible hypotheses, which has to be confirmed by future investigations.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations